Nearly One-Fourth of Eastern Ethiopian Adolescents are Current Psychoactive Substance Users: A School-Based Cross-Sectional Study - Birhanu A; Bete T; Eyeberu A; Getachew T; Yadeta E; Negash A; Lami M; Balcha T; Sertsu A; Deballa A (Dove Medical Press, 2023)
Abdi Birhanu,1 Tilahun Bete,2 Addis Eyeberu,3 Tamirat Getachew,3 Elias Yadeta,3 Abraham Negash,3 Magarsa Lami,3 Tegenu Balcha,3 Addisu Sertsu,4 Adera Deballa3 1School of Medicine, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2Department of Psychiatry, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Department of Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 4Department of Nursing, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Abdi Birhanu, Haramaya University, P.O. Box: 235, Harar, Ethiopia, Email abdiibiree@gmail.comIntroduction: Psychoactive substance use is a growing health problem in both developing and developed countries. Despite adolescents being at high risk of practicing risky behaviors including substance use, there is no adequate information on the problem in the Harari Region, in the Eastern part of Ethiopia. Hence, the present study aimed to identify the burden of current substance use in high school adolescent students of Harari Region, Ethiopia, from 10th April to 10th May 2022.Methods: A school-based cross-sectional study was employed on a total of 1498 randomly selected adolescent students. Poisson regression was used for the assessment of substance use over the last three months among adolescent students. The substance use burden was reported by IRR (incidence rate ratio) at a 95% Confidence interval. The final model fitness was checked using Akaike information criterion (AIC) and Bayesian information criterion (BIC) reports. The variables that had less than 0.05 P-value were declared to be statistically significant.Results: The overall psychoactive substance use was 373 (24.9%, 95% Confidence Interval (CI); 22.8- 27.1%). The substances included khat (21.6%, 95% CI; 18.6- 23.6%), alcohol drinking (1.8%; 95% CI; 1.3- 2.6%), and smoking (1.2%, 95% CI; 0.75- 1.9%). Being male (IRR (Incidence Rate ratio) = 1.21, 95% CI; 1.11- 1.38), availability of the substance (IRR (Incidence Rate ratio) = 2.02, 95%; 1.53- 2.66), having substance user friends (IRR=1.60: 95% CI: 1.30- 2.01), and being at a younger age (IRR = 1.21; 95% CI: 1.02- 1.44) increased the psychoactive substance use rate in the adolescents.Conclusion and Recommendation: One out of four adolescents was a current psychoactive substance user. Being male, substance availability, having substance-user friends, and being at younger age increased the psychoactive substance use rate in school adolescents in Eastern Ethiopia. The intervention that involves the schools' community, students' families, and executive bodies should be strengthened to overcome the substance use-related burdens among high school adolescent students.Keywords: psychoactive substance use, adolescents, students, Ethiopia